I am special : a workbook to help children, teens and adults with autism spectrum disorders to understand their diagnosis, gain confidence and thrive - Vermeulen, Peter; Junor, Beth. (London : Jessica Kingsley Publishers, 2013)
I am Special is a programme for helping children, teens and adults on the autism spectrum to understand themselves and their diagnosis, gain confidence and thrive. Specially-designed worksheets, included on a CD in a handy printable format, are completed to build up a unique and personal book about the individual and promote self-understanding.
Pt. 1. Theory -- pt. 2. Practical manual.
First published in Dutch by EPO Publishers.
A book is acompanied by one computer optical discd entitled'I am special : a workbook to help children, teens and adults with autism spectrum disorders to understand their diagnosis, gain confidence and thrive' bearing the same call number and available at Bahagian Koleksi Media.
Includes bibliographical references and index.
Keywords: Autism spectrum disorders; Autism spectrum disorders in children